Pemikiran Islam Kontemporer , Antara Mode Pemikiran dan Model Pembacaan - Mohammad Muslih (Universitas Darussalam Gontor, 2012)
This paper examines mode of Islamic thought is developing today ,which was then known as Contemporary Islamic Thought, by searching the role of logic and reasoning behind the idea. Three main issues are addressed: first, the project of contemporary Islamic thought, which is a radical reading of the construction of epistemology of sciences and building of logical basic of traditions, culture and civilization, by taking the authentic (al-ashâlah) and inner structure (bunyah),so that it can be transformed to the present. Second,the mode of contemporary Islamic thought, related to attitudes toward tradition (turâts) on the one hand and attitudes towards modernity (hadâtsah) on the other. In contrast to the traditional thought that addressing modernity with a priori for conservation,are also different from modern thought that response to the tradition as something that must be eliminated for the sake of progress; Contemporary Islamic thought involved a critical reading of tradition and modernity ,before bringing them within the framework of contemporary challenges. And third,the model of contemporary readings, by indicate methodological tools of scientific work. Hermeneutics, criticism, and deconstruction are three species of readings that be able to break through the scarcity of methodological for reading complexity of culture and problems of humanity in general, which has not been available instrument for that.